Circular RNA PVT1 expression and its roles in acute lymphoblastic leukemia. (25th April 2018) - Hu, Jiaojiao; Han, Qi; Gu, Yan; Ma, Jinlong; McGrath, Mary; Qiao, Fengchang; Chen, Baoan; Song, Chunhua; Ge, Zheng
Aim: The roles of circular RNA PVT1 ( circPVT1 ) are explored in the patients with acute lymphoblastic leukemia (ALL).Methods: The circPVT1 level was detected by qRT-PCR and western blot. The apoptotic cells were examined by the annexin V assay in lentiviral shRNA knockdown cells.Results: circPVT1 was highly expressed in ALL compared with normal bone marrow samples. circPVT1 expression was also significantly higher in ALL cell lines. circPVT1 knockdown inhibited cell proliferation and induced cell apoptosis through suppression of its neighbor gene c-Myc, and antiapoptotic Bcl-2 protein expression.Conclusion: circPVT1 is upregulated in ALL. Silencing circPVT1 results in cell growth arrest and apoptosis of the cells. Our results also suggested a therapeutic potential of targeting circPVT1 in ALL.